Pemberdayaan Ekonomi di Majelis Zikir Sa’adatuddarain Desa Cikeduk Kabupaten Cirebon - Ali, Muhamad (Empower : Jurnal Pengembangan Masyarakat Islam, 2024)
The presence of a dhikr assembly as a forum for education for the community certainly has a positive impact in overcoming low human resources. One of them is the Sa'adatuddarain dhikr assembly in Cikeduk Village, Cirebon Regency, this is because the majority of people in Cikeduk Village who are over 50 years old have an average education of only up to elementary school (primary school), moreover they do not have an educational background in Islamic boarding schools. So the presence of the Sa'adatuddarain dhikr council tries to be a forum for non-formal education for the Cikeduk people regarding religion and social matters. The aim of this research is to determine the role of dhikr councils in religious and social education for the community. This research includes field research (Field research) using a qualitative approach. The data sources used are primary data sources and secondary data sources. The data collection technique uses observation, interviews, and documentation using technical triangulation to validate the data. Then data analysis which includes data collection, data reduction, data presentation, and drawing conclusions. The results of this research indicate that the role of the Sa'adatuddarain dhikr assembly in religious and social education for the Cikeduk community has been successfully implemented. This can be seen from the success of the congregation when applying the knowledge they have gained from the assembly, including in the field of monotheism such as glorifying Allah SWT and carrying out prayers on time, then in the field of fiqh such as carrying out prayers in accordance with the nature of the Prophet Muhammad's prayers, and in the field of Sufism such as implementing asceticism in daily life and increasing dhikr. Apart from the religious side, there is also a social side which includes commendable morals, a harmonious family and building relationships between congregations. And the characteristic of this assembly is that it acts as an economic mentor by presenting monthly social gatherings in which there are emergency fund savings and business capital loans for the congregation.